Gestion integral de residuos solidos en la tabacalera La Francey S.A. canton Quevedo, Los Rios, Ecuador - Arias Moreira, Tito Alfredo (2014)
This research "Integrated Solid Waste Management in La Tabacalera SA Francey Region Quevedo, Los Rios - Ecuador" aims to develop a technical proposal for Integrated Solid Waste Management in La Tabacalera SA Francey, Quevedo Canton, province of Los Ríos - Ecuador, the current management of solid waste in the La Tabacalera SA Francey was evaluated, for the characterization of solid waste and the number of production of solid waste in every area and every production process in order to identify the type of waste, weight, volume and per capita rate was determined. To evaluate the current system of waste management workshop in order to explain to all staff about the importance of proper waste management later to make a questionnaire for assessing the current status of the company with the view held workers, the results of the questionnaire were tabulated according to the Model Domain - Displays for the type of open reagent dichotomous Instrument with two response options, then proceeded to determine the reliability of dichotomous reagents and calculate the variance for total scores, this information was replaced in formula Kuder - Richardson. For reactive with three options was calculated reliability coefficient called Cronbach's alpha. The Proposal of the Integrated Management System of solid waste is performed based on the results obtained in the characterization and evaluation of waste. We recommend implementing proposed in this research with the aim to achieve the following program objectives: prevent contamination of natural resources for the provision and management of solid waste generated in the business and empower the program to manage solid waste is being executed.